MODEL PENYUSUTAN DARAB JUMLAH PESERTA ASURANSI PADA ASURANSI JIWA - Sunarsih, Sunarsih; Sakinata, Meidar (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2009)
Multiple decrement model in life insurance is a decrement model where the decrement of amount participants of insurance do not only because of just one cause of decrement but because of two or more causes of decrement, so that can provide various benefit in one policy of insurance program. In this paper, using two causes of decrement, that is disability and death. In construction of a multiple-decrement table, can be associated from the tables of single-decrement which have known. The number of premium payments for life insurance depends on what kind of insurance program that have been taken. A life insurance, the number of premium depends on of age, even though onÂ term insurance, except age is policy time period. Â Keywords: Insurance, Multiple Decrement Model